Calculations of the Heave and Pitch RAO’s for Three Different Ship’s Hull Forms - Ghassemi, Hassan; Majdfar, Sohrab; Gill, Valiollah (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2015)
The research carried out in this article is to determine the RAO (Response Amplitude Operator) heave and pitch motions of three different ship’s hulls forms. Ship is running at the head sea of the regular wave and its responses are obtained by modified strip theory using Maxsurf software. Three different ship’s hull forms (Wigley-S60-DDG) are selected in order to predict the results. The obtained results of RAO heave and pitch motions are presented and discussed at various Froude numbers.